Power allocation in wireless asynchronous localization networks‡. Issue 16 (31st August 2016) - Zhang, Tingting; Li, Jiaxiang; Li, Chuanying; Xu, Hongguang; Molisch, Andreas F.
Abstract: Wireless localization systems based on determination of signal runtime, such as time of arrival and time difference of arrival, are of great importance for a variety of applications. In many cases, synchronization of the clocks of the agent nodes to those of the network nodes (anchors) has to be performed together with the localization. The current paper investigates the fundamental accuracy limits of such a joint localization/synchronization. In particular, we analyze the impact of allocating power to the different anchor nodes and optimize this power allocation to maximize accuracy. Optimal trade‐offs between localization and synchronization can be drawn according to the presented frameworks. Simulation results confirm the importance of proper power allocation; known special cases (time difference of arrival localization, localization with already‐synchronized clocks) are recovered from our general solution. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We investigate the fundamental accuracy limits of clock synchronization and localization in wireless networks. Optimal power allocation frameworks are presented to analyze the trade‐offs between clock synchronization and localization and know special cases such as TDOA can be recovered from our general solution.